Vexed. Series 2 [videorecording (DVD)] - Stephens, Toby, 1969-; Raison, Miranda, 1980-; Dunning, Nick, 1959- (Acorn Media, 2013)
A British buddy cop show with a twist. Detectives Jack and Georgina share chemistry but have complicated personal lives.